Arcetri Science Path - Baldanzi, Elisabetta; Barbagli, Fausto; Dominici, Daniele; Gasperini, Antonella; Poggi, Giacomo (Il Colle di Galileo, 2026)
The villa where Galileo Galilei spent the last years of his life stands on the Arcetri hillside, south of Florence. In 1633, the house became his place of forced residence, in accordance with the sentence imposed by the Holy Office. The scientist found comfort in the presence of his followers, who remained with him until his final hours, learning about science from him. In honour of Galileo’s life, various scientific institutes began to establish themselves on the hill in the 19th century. These included the Astronomical Observatory, the University’s Institute of Physics and the National Institute of Optics. These institutions, which in later years changed their names to reflect those of their current parent organisations, have been home to illustrious scientists who gave them the prestige they still enjoy today and which has grown over the years. For these reasons, Arcetri Hill was named a Historic Site of the European Physics Society in 2013. The research institutions based on the hill developed the idea of creating a “science park” in these places, which also benefit from the beauty of the Tuscan landscape. The park includes the recently restored Villa di Galileo and a tour of the various institutes, allowing the dissemination of scientific knowledge of the highest value and historical significance which is still very much alive in the field of state-of-the-art physics research. The paper describes the process behind this initiative and briefly outlines the work already carried out on both the Villa and the institutes, paying tribute to all those who made the project possible, to the support received from the research bodies involved and to the generous support, not only in terms of funding, provided over the years by the Fondazione Cassa di Risparmio di Firenze.